O protagonismo dos apresentadores no contrato de comunicação de programas policiais na Paraíba. - Geronimo, Aderlon dos Santos (2019)
The research aims to understand how Paraíba police presenters develop communication strategies to establish a communication contract. That is, how they act in constructing the narratives of the news reported on police television programs. The analysis comes from four newspapers - and their respective presenters - which are broadcast at noon time in the state of Paraíba: Correio Verdade, Cidade em Ação, Fala Cidade and Tambaú da Gente. The study is based on the concepts of communication contract, performance, credibility, ethos, logos and pathos. Our methodological approach is anchored in participant observation, interviews with presenters, and analysis of the seven drama components identified in the basic structure of police programs (dramatic staging; various news; superficialities; violence, pain, suffering, tragedy; language figures; repetition, fragmentation and speed; construction of proximity). We seek to categorize the role play strategies of the presenters in order to understand how the communication contract is born and maintained in these programs. The results indicate that the presenters take the lead in the news whose content loses relevance to a dramatic performance.